COMPUTER ASSISTED TEST UNTUK PENGELOMPOKAN JABATAN TEKNISI MENGGUNAKAN ALGORITMA K-MEANS (STUDI KASUS : PT. XYZ) - Mohammad Iqbal; Haryati Haryati (Program Studi S1 Sistem Informasi Fakultas Komputer dan Teknik Universitas Alma Ata, 2022)
Computer assisted test to classify technician positions using the K-means algorithm is a system built with the ability to measure abilities as well as determine the area of expertise of technicians at PT. XYZ. The purpose of making this computer-assisted test information system is to improve the technical exam system that is still manual into a computerized technician exam system by changing the procedure into a computer that uses storage media in the form of a database. The computer assisted test information system was created by referring to the SDLC (System Development Life Cycle) method which has the characteristic of working on each phase in Waterfall, which must be completed first before proceeding to the next phase. The system built is a website-based application that has two main interfaces, namely the admin interface and the technician interface. Admin interface that functions to manage users or technicians, manage question banks and manage test scores. While the User interface serves to work on exam questions. The test score data will be processed by the K-means algorithm to determine the area of expertise of each technician. This research was conducted by Muhamad Ramadhan, a student of the 2020 POLSUB information systems study program. M. Ramadhan assessed the suitability of the system with the design made by testing the system using black box testing which showed 100% success of system functionality and User Acceptences Testing (UAT) which showed ergonomic values. which is quite high at 93.25%.